Relationship between work-family conflict and work, family and community domains demands and resources : A longitudinal study - Zaiton, binti Hassan; Surena, Binti Sabil; Nur Fatihah, Bin Abdullah Bandar; Dayang Kartini, Binti Abang Ibrahim; Nik Norsyamimi, Binti Md Nor (Science Publishing Corporation Inc., 2018)
Shifting from Western-dominated perspectives, demands and resources from the community domain were investigated, together with work and family domains to predict work-family conflict and family-work conflict. Pearson correlation analysis was conducted on data obtained through two self-report questionnaires completed three months apart by 277 executives and non-executives from three public and private sector organizations in Sarawak, East Malaysia. After controlling for conflict at Time 1, work demands were positively related; while work resources were negatively related to work-family conflict and family work conflict at Time 2. In addition, community demands were related positively to work-family conflict and family work conflict at Time 2. This study underscores the roles of community which has been neglected in Western studies, as important in affecting work-family conflict and family-work conflict in Malaysia. Therefore, to improve our understanding on work-family conflict in a society which is predominantly collectivist, aspects of community should be included